Research of subpopulation CD3+ CD4- CD8- double-negative T lymphocytes in kidney transplant recipients - S. V. Zybleva; S. L. Zyblev (Трансплантология (Москва))
Introduction. CD3+CD4- CD8- cells represent one of the subpopulations of T-regulatory lymphocytes. According to literature reports, an increase in the content of graft-infiltrating CD3+CD4- CD8- T cells was detected in the heart xenograft tissues of an experimental model with a long-term graft survival. The efficacy of CD3+CD4- CD8- infusion to induce skin graft tolerance was described. Some studies have shown that a decrease in CD3+CD4- CD8- content in peripheral blood of patients undergoing to hematopoietic stem cell transplantation was associated with the development of a graft-versus-host reaction.Objectives. To study changes in the values of CD3+CD4- CD8- double-negative T lymphocytes in peripheral blood in kidney transplant recipients.Material and methods. The study included 165 recipients who underwent kidney transplantation. The creatinine and urea concentrations in blood were determined before surgery, on day 7, and day 360 after transplantation. The content of CD3+CD4- CD8- lymphocytes was studied before surgery, on the 3rd, 7th, 30th, 90th, 180th and 360th days after surgery. Early graft function was assessed on day 7 after transplantation. The function was defined as a primary one at creatinine levels below 300 μmol/L. The graft dysfunction was defined as creatinine values equal to or greater than 300 μmol/L and the need for dialysis in the first week after surgery. The satisfactory graft function after a year was characterized by the blood creatinine level below 150 μmol/L, absent episodes of graft rejection, and no need for dialysis in the first year of follow-up. There were 4 groups of recipients formed. The first group included patients with the primary graft function and satisfactory late graft function. The second group included patients with the primary function and late graft dysfunction. The third group included patients with the primary dysfunction and late satisfactory function. The fourth group included patients with the primary and late graft dysfunction.Results. In the first and second groups, there were no significant differences in the blood level of CD3+CD4- CD8- during the year. After a year, a significant CD3+CD4- CD8- decrease was noted in the group with late graft dysfunction. A similar tendency was revealed in the third and fourth groups. In the fourth group (with late graft dysfunction), the level of CD3+CD4- CD8- was significantly lower only after a year of observation compared with the levels in the third group. A negative correlation was noted between the CD3+CD4- CD8- values and the creatinine and urea levels. Thus, high CD3+CD4- CD8- values in kidney transplant recipients after a year were associated with a satisfactory graft function.Conclusions. 1. A stable 1-year satisfactory kidney graft function is characterized by an increase in the blood level of CD3+CD4- CD8- T lymphocytes. 2. A kidney graft dysfunction in the late post-transplant period is characterized by a decrease in the blood level of CD3+CD4- CD8- T lymphocytes.Authors declare no conflict of interest.